Corticoreticular Tract in the Human Brain: A Mini Review - Jang, Sung Ho; Lee, Sung Jun (Frontiers in Neurology, 2019)
Previous studies have suggested that the corticoreticular tract (CRT) has an important role in motor function almost next to the corticospinal tract (CST) in the human brain. Herein, the CRT is reviewed with regard to its anatomy, function, and recovery mechanisms after injury with particular focus on previous diffusion tensor tractography-based studies. The CRT originates from several cortical areas but mainly from the premotor cortex. It descends through the subcortical white matter antero-medially to the CST with a 6 to 12 mm separation in the antero-posterior direction, then passing through the mesencephalic tegmentum and the pontine and pontomedullary reticular formations. Regarding its motor functions, the CRT appears to be mainly involved in the motor function of proximal joint muscles accounting for approximately 30 40% of the motor function of these joint muscles. In addition, the CRT is involved in gait function and postural stability. However, further studies that clearly rule out the effects of other motor function-related neural tracts are necessary to clarify the precise portion of the total motor function for which the CRT is responsible. With regard to recovery mechanisms for an injured CRT, three recovery mechanisms were suggested in five previous studies: recovery through the original pathway, recovery through peri-lesional reorganization, and recovery through the transcallosal pathway. However, each of those studies was single case reports; therefore, further original studies including a larger number of patients are warranted.